Acesso à justiça enquanto direito fundamental: efetivação pela defensoria pública - Amorim, Ana Mônica Anselmo de (2011)
The Federal Constitution of 1988 is recognized for its enlargement in the face of large amount of provisions that make it up, among which many are fundamental rights. The fundamental rules set up the foundation of a democratic state, however, are the necessary legal mechanisms to be effective, its exercise is not enough merely to state them, but to offer ways for them to stop being just written standard on paper, and come to be viewed and exercised day-to-day. In this sense, access to justice presents itself in our times, as a cornerstone for a just society dictates. In this light, access to justice can be seen as the most fundamental of rights, which translates as instruments able to safeguard the fundamental rights not only against the action/omission violating the state but also the very particular. Furthermore, access to justice within the legal country, is not right for everyone, despite the willingness of the Citizen Charter in its article 5, paragraph LXXIV, ensuring that the State shall provide full and free legal assistance to those in need. More than half of the population lives in poverty and can´t afford to pay legal fees or court costs as well as a bump in their own ignorance of their rights. The judiciary, in their primary function, is in charge of trying to correct the violation of the rights, intending to effect a true distributive justice, serving as a paradigm for the promotion of substantive equality of human beings, however, is difficult and tortuous access Justice for those without financial resources. In this vein, we present the Public Defender, as keeper of the masses in its institutional role, defending a disadvantage, in the words, as a mechanism for effective access to justice, ensuring therefore fundamental rights. Public Defenders arise at the time or much discussion highlights the priority of actual access to justice, custody, therefore, intimate bond with the pursuit of fundamental rights, in which, that advance the broad range of rights, without whom could defend them or guardianship them